2018
DOI: 10.1128/aem.01390-18
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity and Diversity of Complete Ammonia Oxidizers (Comammox)

Abstract: The discovery of complete ammonia oxidizers (comammox) refutes the century-old paradigm that nitrification requires the activity of two types of microbes. Determining the distribution and abundance of comammox in various environments is important for revealing the ecology of microbial nitrification within the global nitrogen cycle. In this study, the ubiquity and diversity of comammox were analyzed for samples from different types of environments, including soil, sediment, sludge, and water. The results of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
149
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 41 publications
(58 reference statements)
14
149
0
1
Order By: Relevance
“…The divergence of CAOB amoA hindered the development of the universal primer set covering both clades. The primer set targeting only clade A had been designed to quantify CAOB in wastewater treatment systems and other ecosystems (Wang et al, 2018; Xia et al, 2018). The sister primer sets target clade A and clade B were separately developed for identifying CAOB, although nonspecific amplifications were reported (Pjevacet al 2017; Keene-Beach and Noguera, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergence of CAOB amoA hindered the development of the universal primer set covering both clades. The primer set targeting only clade A had been designed to quantify CAOB in wastewater treatment systems and other ecosystems (Wang et al, 2018; Xia et al, 2018). The sister primer sets target clade A and clade B were separately developed for identifying CAOB, although nonspecific amplifications were reported (Pjevacet al 2017; Keene-Beach and Noguera, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A newly designed primer set specifically targeting the clade A of CAOB amoA gene revealed high abundances of CAOB in full-scale WWTPs (Wang et al, 2018). Likewise, a clade A targeted primer set was designed to quantify the CAOB abundances in various environments (Xia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By now, comammox Nitrospira were also detected in several natural environments, including lake sediment and forest and agricultural soils (Orellana et al ., ; Parks et al ., ; Pjevac et al ., ; Xia et al ., ). Notably, in fertilized soils (Orellana et al ., ) and acidic subtropical forest soils (Shi et al ., ), the increased abundances of comammox Nitrospira in response to human‐induced N loadings indicate that they can drive nitrification also under less oligotrophic conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Notably, in fertilized soils (Orellana et al ., ) and acidic subtropical forest soils (Shi et al ., ), the increased abundances of comammox Nitrospira in response to human‐induced N loadings indicate that they can drive nitrification also under less oligotrophic conditions. The observed diversity together with the identification of comammox Nitrospira as the most abundant nitrifiers in acidic forest soil (Hu and He, ) as well as in estuary and coastal environments (Xia et al ., ) indicates their vital contribution to nitrification also in natural systems. However, comammox Nitrospira genomes from natural environments were rarely recovered and analysed so far, and thus the metabolic capabilities of complete nitrifiers in these ecosystems are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The three reported comammox species, Nitrospira inopinata , Candidatus Nitrospira nitrificans and Candidatus Nitrospira nitrosa, form a cluster (clade A) in a phylogenetic tree for the amino acid sequences of AmoA (Daims et al ; van Kessel et al ). Comammox clade A is further divided into two monophyletic groups, clades A.1 and A.2, and the identified comammox species are present in clade A.1 (Xia et al ). Another cluster (clade B) has been proposed based on amoA gene sequences from groundwater metagenome bins (Daims et al ); however, their complete nitrification activities have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%